Using intervention mapping to develop a home-based parental-supervised toothbrushing intervention for young children. (December 2015) - Gray-Burrows, K.; Day, P.; Marshman, Z.; Aliakbari, E.; Prady, S.; McEachan, R.
Abstract Background Dental caries in young children is a major public health problem impacting on the child and their family in terms of pain, infection and substantial financial burden on healthcare funders. In the UK, national guidance on the prevention of dental caries advises parents to supervise their child's brushing with fluoride toothpaste until age 7. However, there is a dearth of evidence-based interventions to encourage this practice in parents. The current study used intervention mapping (IM) to develop a home-based parental-supervised toothbrushing intervention to reduce dental caries in young children. Methods The intervention was developed using the six key stages of the IM protocol: (1) needs assessment, including a systematic review, qualitative interviews, and meetings with a multi-disciplinary intervention development group; (2) identification of outcomes and change objectives following identification of the barriers to parental-supervised toothbrushing (PSB), mapped alongside psychological determinants outlined in the Theoretical Domains Framework (TDF); (3) selection of methods and practical strategies; (4) production of a programme plan; (5) adoption and implementation and (6) Evaluation. Results The comprehensive needs assessment highlighted key barriers to PSB, such as knowledge, skills, self-efficacy, routine setting and behaviour regulation and underlined the importance of individual, social and structural influences. Parenting skills (routine setting and the ability to manage the behaviour of a reluctant child) were emphasised as critical to the success of PSB. The multi-disciplinary intervention development group highlighted the need for both universal and targeted programmes, which could be implemented within current provision. Two intervention pathways were developed: a lower cost universal pathway utilising an existing national programme and an intensive targeted programme delivered via existing parenting programmes. A training manual was created to accompany each intervention to ensure knowledge and standardise implementation procedures. Conclusions PSB is a complex behaviour and requires intervention across individual, social and structural levels. IM, although a time-consuming process, allowed us to capture this complexity and allowed us to develop two community-based intervention pathways covering both universal and targeted approaches, which can be integrated into current provision. Further research is needed to evaluate the acceptability and sustainability of these interventions.